2018
DOI: 10.1016/j.toxrep.2018.08.011
|View full text |Cite
|
Sign up to set email alerts
|

A risk assessment study of the occurrence and distribution of aflatoxigenic Aspergillus flavus and aflatoxin B1 in dairy cattle feeds in a central northern state, Nigeria

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
0
13
2
2
Order By: Relevance
“…Rodrigues et al [21] reported the highest level of AF in compounded dairy feed and raw materials for making compounded feed in Nigeria at 435.9 µg/kg and a mean of positive of 115 µg/kg [21]. However, another study by Omeiza et al [35] on compounded dairy feed and pasture showed a lower mean of 10.5 µg/kg, with 66.4% of the samples exceeding the EU regulatory limit. In the study, concentrates had the highest incidence of AFB1 at 93% with dry pasture having 60% and pasture mixed with concentrates having an incidence of 86.9%, indicating concentrates as the major source of AF.…”
Section: West Africamentioning
confidence: 96%
See 1 more Smart Citation
“…Rodrigues et al [21] reported the highest level of AF in compounded dairy feed and raw materials for making compounded feed in Nigeria at 435.9 µg/kg and a mean of positive of 115 µg/kg [21]. However, another study by Omeiza et al [35] on compounded dairy feed and pasture showed a lower mean of 10.5 µg/kg, with 66.4% of the samples exceeding the EU regulatory limit. In the study, concentrates had the highest incidence of AFB1 at 93% with dry pasture having 60% and pasture mixed with concentrates having an incidence of 86.9%, indicating concentrates as the major source of AF.…”
Section: West Africamentioning
confidence: 96%
“…AF and FUM were the most prevalent mycotoxins in Ghana (72% and 94%, respectively) and Nigeria (100% and 89%, respectively) [21,35]. Rodrigues et al [21] reported the highest level of AF in compounded dairy feed and raw materials for making compounded feed in Nigeria at 435.9 µg/kg and a mean of positive of 115 µg/kg [21].…”
Section: West Africamentioning
confidence: 99%
“…In 1993, the International Agency for Research on Cancer (IARC) determined there was sufficient evidence to classify AFB 1 as a group 1 human carcinogen [3,4]. Further, recent and ongoing risk assessments have confirmed to impact of AFB 1 in human health and as an ongoing exposure problem in people as well as in plant and animal foods for human consumption [[5], [6], [7], [8]]. Covalent adduction of AFB 1 to lysine residues in serum albumin (AFB 1 -lys) represents a biomarker of internal dose, which reflects recent dietary exposure (up to ˜3 months) and has been strongly associated with several health outcomes such as growth stunting in children and liver cancer [[8], [9], [10], [11]].…”
Section: Introductionmentioning
confidence: 99%
“…A ocorrência de AFLAs têm sido relatada em grãos, rações e silagem de grãos (MOSS, 1998;O'BRIEN et al, 2005;SASSAHARA;NETTO;YANAKA, 2005;OMEIZA et al,2018;DADZIE et al, 2019), sendo preocupante, uma vez que o sistema digestivo dos animais não é suficiente para degradar essas toxinas (OBREMSKI et al, 2009). A metabolização da AFLAB 1 ocorre no fígado, através de um conjunto de enzimas do citocromo P 450 , que são consideradas hemoproteínas e têm como função a conversão desses compostos…”
Section: Aflatoxinas Em Leite E Produtos Lácteosunclassified